Experimental Investigation into the Bedding Plane Slip Effect on the Overlying Strata Behavior in Longwall Top Coal Caving of Soft Coal Seam - Hengfeng Liu; Jixiong Zhang; Nan Zhou; Qiang Sun; Meng Li; Zhizhong Cui (Advances in Civil Engineering)
Bedding plane shear slip becomes more obvious in rock strata with quite different mechanical properties. A composite beam model considering the behaviors of the main roof and the immediate roof in the “three-soft” coal seam is established based on physical similarity simulation experiments and the slip theory in this paper. The movement and failure of the overlying strata and the mechanism of the bedding plane slip at the 2211 working face are studied by experimental and theoretical analysis. The results suggest that the front abutment stress distribution occurs 50 m ahead of the working face, the initial caving interval of the main roof is 55 m, and the peak stress appears at a distance 20 to 32 m ahead of the working face. The bedding plane slip areas can be divided into the obvious slip area and the slight slip area along the mining direction. The range of the obvious slip area becomes wider and the range of the slight slip area grows to be narrower as the working face advances. The bedding plane slip becomes steady after gradual increase and leads to the subsidence of the overlying strata in the “three-soft” coal seam. The observed initial caving interval of the main roof by field measurement is 51 m, which is consistent with the results of physical similarity simulation experiments and theoretical analysis. The results demonstrate that the beam slip model proposed in this paper is reasonable and able to describe the behaviors of overlying strata and bedding plane slip.